Pendidikan Islam dalam Turbulensi Era 4.0 - Adun Priyatno (Al-Fikr: Jurnal Pendidikan Islam, 2020)
The challenges faced by the educational world become more complex. Due to the present digitalization era, education is required to adjust to the existence of technological advancementby integrating technology into its educational systems. Modernization of Islamic educations hasrecently become a certainly and should be realized in all educational aspects starting from itseducation curriculums, educational institutions managements, learning models and strategies usedcreate education which is in accordance with the need of this era. Within those advancements,character education has become an oasis in the middle of morality decadences of millennialgeneration in the present society and a fort to prevent the destruction of a nation. Thethe research method uses literature study by collecting data from documentation using descriptive analysis method. The results of the study can be concluded, Islamic education transformation isgreatly required to gain solutions from the arising crisis and problems. Strengthening Islamiceducational institutions also require more attention, including strengthening the Islamiceducational management, Islamic educational leadership, and educational policy reform which isintended to create an intact generation as well as excellent and competitive human resources withcreativity, innovations, character, independence, nationality, and religiously in facing theturbulence era 4.0 where humans are expected to be fast, accurate, effective, and efficient.